Analisis kredit bermasalah ditinjau dari non performing loan (NPL) pada PT Bank Mandiri (persero) Tbk - Gunardi, Gunardi; Karyadi, Karyadi; Pujianti, Anisya; Zahra, Shafira; Ksatria, Panji; Munggaran, M.Zakky; Hanifah, Salma; Ikhsan, Sugiyanto (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2022)
As we know, in the financial system, there are various financial institutions that act as financial intermediaries. That is, lending money from the savings and loan community, lending it back to other parties. This is because it does not rule out the possibility that credit will pose a risk for this research to assess how much non-performing loans are in terms of non-performing loans (NPL) in a banking company, namely PT Bank Mandiri (Persero) Tbk. The method used in this research is the descriptive method. The sources of data used are secondary data and the use of library research and observation techniques as data collection techniques. In this study, we used a non-performing loan (NPL) financial ratio calculator as a data analysis technique. From this study, it was concluded that the highest NPL ratio occurred in 2016 at 3.96% and the lowest NPL ratio occurred in 2019 at 2.39%. The average NPL for the 5 years starting from 2016-2020, which is 3.17%, is in the healthy predicate.